Rola badań marketingowych w kształtowaniu orientacji na konsumenta (na przykładzie firm usługowych) - Dąbrowska, Anna; Janoś-Kresło, Mirosława; Mróz, Bogdan (Role of Marketing Research in the Process of Elaboration of Consumer-Driven Marketing Strategies, 2006)
Professional market research seems to be a major precondition of success of company's marketing effort. It enables the company to gain advantage over rivals in a highly competitive market environment.In the article the role of market research in the process of elaboration of consumer-driven marketing strategies is analysed. In the final section of the paper the authors present and discuss findings of their own empirical research conducted among 310 Warsaw service companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 377-386